The Influence of Work Discipline, Organizational Commitment and Motivation on Employee Performance - Natasya, Rafika; Harini, Sri; Maulana, Lucky Hikmat (MultiTech Publisher, 2024)
Employee performance is one of the main factors that can influence a company's progress. The higher the employee's performance, the easier it will be to achieve the company's goals. The level of work discipline, organizational commitment and motivation will greatly influence performance employees at a company. This research aims to determine the influence of work discipline, organizational commitment and motivation on employee performance at PERUMDA Tirta Pakuan, Bogor City. The method used in this research is descriptive and verification. The sampling technique was carried out by distributing questionnaires to 60 employees. The questionnaire was tested using validity tests, reliability tests and classical assumption tests. The data analysis used is multiple linear regression analysis, analysis of the coefficient of determination as well as the F-test and t-test. test results concluded that was simultaneous and partial variables discipline work, commitment organization, motivation influence positive and are significant to employee performance at PERUMDA Tirta Pakuan Bogor City.